Substituting star grass with corn fodder in Bali Heifer Diets: Impact on intake, digestibility, nitrogen balance, and blood profile - JALALUDIN, JALALUDIN; NIKOLAUS, TARA TIBA; SABAT, DIANA MELIANI; SETYANI, NI MADE PARAMITA (Asian Journal of Agriculture, 2025)
Abstract. Jalaludin, Nikolaus TT, Sabat DM, Setyani NMP. 2025. Substituting star grass with corn fodder in Bali Heifer Diets: Impact on intake, digestibility, nitrogen balance, and blood profile. Asian J Agric 9: 881-888. This study aimed to evaluate the substitution of Star Grass Silage (SGS) with hydroponic Corn Fodder (CF) in the diets of Bali heifers, with a focus on feed intake, nutrient digestibility, nitrogen retention, and blood profile parameters. Hydroponic corn fodder was assessed as a sustainable alternative to star grass silage for Bali heifers, which are typically raised in dry tropical regions characterized by seasonal forage scarcity. Previous studies on the use of corn fodder have predominantly focused on dairy cattle, buffaloes, or goats; therefore, this study provides novel information on Bali heifers in terms of intake, digestibility, nitrogen retention, and blood profiles to determine the optimal substitution level. The experiment employed a 4 × 4 Latin square design with four dietary treatments, consisting of the replacement of SGS with CF at levels of 0%, 20%, 40%, and 60%. The results showed that CF substitution significantly affected (P < 0.05) nitrogen intake and nitrogen retention, with the highest values observed at the 20% CF substitution level, while increasing the substitution to 60% resulted in reduced nitrogen intake and retention. In contrast, CF substitution had no significant effect (P > 0.05) on dry matter, organic matter, and crude protein intake, nutrient digestibility, or blood profile parameters. It was concluded that hydroponic corn fodder can effectively replace star grass silage at substitution levels of 20-40% of the forage portion without impairing nutrient utilization or physiological balance. These findings highlight the potential of hydroponic corn fodder as a forage resource to support the sustainability of Bali cattle production in tropical regions with limited forage availability, particularly during the dry season.